PERTANGGUNGJAWABAN PIDANA MUCIKARI DAN PENGGUNA JASA DALAM PROSTITUSI ONLINE ANAK - Fafirani, Laila Nur; Lukitasari, Diana (Recidive : Jurnal Hukum Pidana dan Penanggulangan Kejahatan, 2022)
Abstract: This article aims to analyze the criminal liability of pimps and service users in child online prostitution in the perspective of the laws and regulations in force in Indonesia and the legal protection of children as victims of online prostitution. This research is a prescriptive normative legal research, in which this normative legal research uses a statutory approach and a case approach. The technique of collecting legal materials is carried out by means of library research, as well as the method of analyzing legal materials using qualitative legal materials analysis methods. Data obtained from primary data and secondary data. The results of the study indicate that there is no law that regulates in detail about online prostitution, especially child online prostitution. The Criminal Code only regulates the punishment of pimps, not with service users and the Criminal Code cannot tackle online prostitution. However, there are several laws and regulations outside the Criminal Code that can be used as a legal umbrella for the criminal liability of pimps and sex service users in the crime of child online prostitution, which is found in Law no. 35 of 2014, Law no. 44 of 2008, Law no. 19 of 2016 jo. Law No. 11 of 2008, Law no. 21 of 2007 and several regional regulations that regulate the same thing. Regarding the legal protection of children as victims of online prostitution, it is divided into 2 (two), namely preventive and repressive legal protection.Keywords: criminal liability; pimping; child online prostitution.  Abstrak: Artikel ini bertujuan untuk menganalisis pertanggungjawaban pidana mucikari dan pengguna jasa dalam prostitusi online anak dalam perspektif peraturan perundang-undangan yang berlaku di Indonesia dan perlindungan hukum pada anak selaku korban prostitusi online. Penelitian ini merupakan penelitian hukum normatif yang bersifat preskriptif, yang mana penelitian hukum normatif ini menggunakan pendekatan perundang-undangan dan pendekatan kasus. Teknik pengumpulan bahan hukum dilakukan dengan cara studi kepustakaan (library research), serta metode analisis bahan hukum menggunakan metode analisis bahan hukum kualitatif. Data diperoleh dari dari data primer dan data sekunder. Hasil penelitian menunjukkan bahwa belum ada undang-undang yang mengatur secara rinci tentang prostitusi online, terlebih prostitusi online anak. KUHP hanya mengatur pemidanaan pada mucikari, tidak dengan pengguna jasa serta KUHP tidak dapat menanggulangi tindak pidana prostitusi online. Namun terdapat beberapa peraturan perundang-undangan di luar KUHP yang dapat dijadikan sebagai payung hukum pertanggungjawaban pidana mucikari dan pengguna jasa seks dalam tindak pidana prostitusi online anak, yang ditemukan dalam Undang-Undang No. 35 Tahun 2014, Undang-Undang No. 44 Tahun 2008, Undang-Undang No. 19 Tahun 2016 jo. Undang-Undang No. 11 Tahun 2008, Undang-Undang No. 21 Tahun 2007 dan beberapa Peraturan Daerah yang mengatur hal yang serupa. Terkait perlindungan hukum anak selaku korban prostitusi online dibagi menjadi 2 (dua), yakni perlindungan hukum preventif dan represif.Kata kunci: pertanggungjawaban pidana; mucikari; prostitusi online anak.